Association of increased participation in social activity in later life with risk of all-cause mortality and heart diseases in older people: results from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) - Wang, Ziqiong; Chen, Changchun; Ruan, Haiyan; He, Sen (Frontiers in Public Health, 2024)
Background: Previous studies have shown social activity is associated with reduced risk of health outcomes. However, among older people (≥ 65 years) who were socially inactive at baseline, limited study explored whether increased participation in social activity in later life was associated with reduced risk of health outcomes; therefore, using the data from the Chinese Longitudinal Healthy Longevity Survey, the study was performed.The study outcomes were 10-year all-cause mortality (sample number = 9984) and 10-year heart diseases (sample number = 7496). The exposure was the change of social activity frequency. Cox regression analysis was used for data analysis.Results: During the follow-up, there were 6407 all-cause mortalities and 1035 heart diseases, respectively. Kaplan-Meier analysis demonstrated that cumulative incidences of all-cause mortality were significantly lower in participants with changes into more frequent social activity (log-rank p < 0.001), while no significant difference was observed for heart diseases (log-rank p = 0.330). Compared with the subgroup who never participated in social activity at baseline, adjusted HRs of all-cause mortality were 0.79 (95% CI: 0.70-0.90, p < 0.001), 0.78 (95% CI: 0.63-0.96, p = 0.019), 0.74 (0.59-0.92, p = 0.006), and 0.70 (95% CI: 0.56-0.88, p = 0.002) for the subgroup of switching to sometimes, the subgroup of switching to once a month, the subgroup of switching to once a week, and the subgroup of switching to everyday, respectively. The corresponding HRs of heart diseases were 0.83 (95% CI: 0.65-1.08, p = 0.170), 0.82 (95% CI: 0.51-1.31, p = 0.412), 0.91 (0.58-1.42, p = 0.675) and 0.75 (95% CI: 0.47-1.20, p = 0.227), respectively. Stratified and sensitivity analyses revealed similar results.Conclusions: Among older people who never participated in social activity, increased participation in social activity in later life was associated with reduced risk of all-cause mortality, but was not associated with reduced risk of heart diseases.